Jekyll or Hyde?: examining the criminal careers of public violence offenders - Ham, Tom van (European journal of criminology, 2017)
Since the 1970s theoretical and empirical work on public violence has mainly focused on the context in which public violence takes place, assuming that public violence offenders are ordinary people acting in extraordinary circumstances. Recent studies however indicate that ‘hooligans’ share many characteristics with other violent offenders, which has (re)fuelled the notion that individual propensity is important in explaining public violence, and that public violence offenders generally fit the small group of serious and persistent offenders identified by Moffitt. Based on Dutch police data on 438 individuals involved in public violence, we examined the criminal careers of public violence offenders leading up to the date of registration as a public violence offender. Using group-based models, we distinguished three criminal career trajectories in our sample. Although we found many public violence offenders had no criminal records whatsoever, we also found a small group of public violence offenders who exhibited a high frequency of offending, displayed both solo and group violence, and acted violently across different settings. Our results leave us to take a middle ground in the context-propensity debate, because we argue that different categories of public violence offenders may exist whose behaviour is triggered by different processes. Incorporating the notion of different types of public violence offenders helps explain the seemingly contradictory findings of prior studies, and suggests new avenues for future research into the intra- and intergroup dynamics of public violence.